Predictability of Successful Induction of Labour with Poor Bishop Score - Tehseen, Saema; Chughtai, Faiqa; Riffat, Najia (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the percentage of successful induction of labour in patients with poor Bishop Score at PAC Hospital Kamra. Study design: Prospective Observational Study. Setting & duration: Pakistan Aeronautical Complex Hospital Kamra, four years from 01.01.2016 till 31.12.2019. Methods: All booked pregnant women including Primigravidaeand Multigravidae were offered induction of labour regardless of Bishop Score to assess the predictability of successful induction. Results: All pregnant ladies booked at Pakistan Aeronautical Complex were induced at term regardless of favourability of Bishop Score and parity. Total number of patients included in the study over four years was 403.Out of these 1280(32%) were primigravidae and 2723(67%) were multigravidae. Successful induction was achieved in 883(68.5%) of primigravidae and was even higher in multigravidae where it was 2205(78.25%). It was found that the success rate of induction in case of favorable and unfavorable bishop score was not significantly different. Out of 665 primigravidae with favorable bishop score 521 delivered which makes 78.3% while 362 out of 615 primigravidae with unfavorable bishop score delivered successfully which makes 58.8%. Conclusion: We offered Induction of labour to all pregnant women regardless of Bishop Score and parity. A Bishop score of seven or less is considered unfavorable whereas a Bishop score of eight or more is considered favorable for induction of labor.